STRATEGI PEMBELAJARAN UNTUK MENGOPTIMALKAN PERKEMBANGAN ANAK USIA DINI PADA MASA ADAPTASI KEBIASAAN BARU DI KECAMATAN SUKASADA, KABUPATEN BULELENG - Komang Trisna Mahartini; Made Adi Nugraha Tristaningrat (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2021)
The purpose of this study was to describe (1) learning strategies to optimize early childhood development during the adaptation period for new habits in Sukasada District, Buleleng Regency; (2) constraints faced in implementing learning strategies to optimize early childhood development during the adaptation period of new habits in Sukasada District, Buleleng Regency; and (3) the efforts made in overcoming obstacles in the implementation of learning strategies to optimize the development of early childhood education during the adaptation period for new habits in Sukasada District, Buleleng Regency. This research is a qualitative descriptive study. The research location is a kindergarten in Sukasada District, Buleleng Regency. The research subjects were Early Childhood Education learning documents in Sukasada District, Buleleng Regency and from informants. The data used in the study consisted of primary data and secondary data. The technique of determining the informants is purposive sampling technique. Data collection techniques by means of interviews, literature study, and document study. Data analysis techniques include data collection, data reduction, data display, and data verification. The results of the study revealed that the Early Childhood Education learning strategy during the adaptation period of new habits in Sukasada District, Buleleng Regency was carried out by blended learning. The obstacles faced arise from teachers, parents, and students. Efforts that can be made are optimizing blended learning and approaching parents of students to establish an understanding of learning strategies in the COVID-19 pandemi situation.